2010
DOI: 10.1590/s1980-65232010000400014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of accessory furcation canals of permanent mandibular molars using radiography and clearing

Abstract: Purpose: To evaluate the presence of furcation canals of permanent mandibular teeth using radiography and a clearing technique. Methods: The sample comprised 344 extracted mandibular molars. The presence of furcation canals was assessed by a single trained observer using magnifying lens (4x) for the dental radiographs and a dental optical microscope (30x) for the cleared specimens. Scanning electron microscopy (SEM) was used to evaluate morphological differences in the pulp chamber floor. Results: Radiographs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Accessory canals have been intensively studied in permanent teeth using radiographs. Harb et al . observed 9% canals in the furcation with another 2.3% probable canals when 344 permanent mandibular molars were evaluated under a standard radiographic examination and a subsequent magnification of 4x using a magnifying lens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accessory canals have been intensively studied in permanent teeth using radiographs. Harb et al . observed 9% canals in the furcation with another 2.3% probable canals when 344 permanent mandibular molars were evaluated under a standard radiographic examination and a subsequent magnification of 4x using a magnifying lens.…”
Section: Discussionmentioning
confidence: 99%
“…The methods to evaluate accessory canals in both permanent and primary teeth include radiography 4 , histological sectioning 5 , topographical studies 6,7 , latex perfusion 8 and methylene blue dye under vacuum 9 to name a few. The prevalence of accessory canals in primary molars varies from 9% to 94% when different methods are employed [4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies reported the presence of chamber canals in premolar and molar teeth, with the highest percentage in first molars ( 17 , 20 ), reaching up to 13% in mandibular first molars ( 17 ); this was consistent with one study on primary molars ( 24 ). However, other studies did not identify furcation canals ( 18 , 22 ). Indeed, staining followed by decalcification has technical limitations such as inconsistent demineralisation for samples of different weight/volume and sample loss because of cracking, deterioration and pulp dissolution after immersion in strong acids ( 22 , 25 ).…”
Section: Introductionmentioning
confidence: 94%
“…However, other studies did not identify furcation canals ( 18 , 22 ). Indeed, staining followed by decalcification has technical limitations such as inconsistent demineralisation for samples of different weight/volume and sample loss because of cracking, deterioration and pulp dissolution after immersion in strong acids ( 22 , 25 ).…”
Section: Introductionmentioning
confidence: 94%